PRMT5 silencing selectively affects MTAP‐deleted mesothelioma: In vitro evidence of a novel promising approach. Issue 10 (17th April 2020) - Barbarino, Marcella; Cesari, Daniele; Bottaro, Maria; Luzzi, Luca; Namagerdi, Asadoor; Bertolino, Franca Maria; Bellan, Cristiana; Proietti, Fabrizio; Somma, Pasquale; Micheli, Mariacarolina; de Santi, Maria Margherita; Guazzo, Raffaella; et al.
Abstract: Malignant mesothelioma (MM) is an aggressive asbestos‐related cancer of the serous membranes. Despite intensive treatment regimens, MM is still a fatal disease, mainly due to the intrinsic resistance to current therapies and the lack of predictive markers and new valuable molecular targets. Protein arginine methyltransferase 5 (PRMT5) inhibition has recently emerged as a potential therapy against methylthioadenosine phosphorylase (MTAP)‐deficient cancers, in which the accumulation of the substrate 5'‐methylthioadenosine (MTA) inhibits PRMT5 activity, thus sensitizing the cells to further PRMT5 inhibition. Considering that the MTAP gene is frequently codeleted with the adjacent cyclin‐dependent kinase inhibitor 2A ( CDKN2A ) locus in MM, we assessed whether PRMT5 could represent a therapeutic target also for this cancer type. We evaluated PRMT5 expression, the MTAP status and MTA content in normal mesothelial and MM cell lines. We found that both administration of exogenous MTA and stable PRMT5 knock‐down, by short hairpin RNAs (shRNAs), selectively reduced the growth of MTAP ‐deleted MM cells. We also observed that PRMT5 knock‐down in MTAP ‐deficient MM cells reduced the expression of E2F1 target genes involved in cell cycle progression and of factors implicated in epithelial‐to‐mesenchymal transition. Therefore, PRMT5 targeting could represent a promising new therapeutic strategy against MTAP ‐deleted MMs.